Race and assessment in higher education : from conceptualising barriers to making measurable change - Campbell, Paul Ian (Emerald Publishing Limited, 2024)
In addition to helping us make sense of a deeply complex issue, Race and Assessment in Higher Education: From Conceptualising Barriers to Making Measurable Change provides us with proven guidance for what works in addressing race-based inequities in higher education assessment and what we can do to promote greater racial inclusivity in this space. Mapping the experiences of 104 racially minoritised and white undergraduate students in UK universities, author Paul Campbell examines racial barriers in assessment and varying experiences of inclusion for students of colour to create a framework for addressing these barriers. Drawing on qualitative stories and quantitative data from over 175 students, Campbell explores the direct, positive impact of this framework for improving students' experiences of racial inequity and reducing the race award gap in degree outcomes. Offering the first direct, evidence-based response on the challenges faced by students of colour in higher education assessments in the UK, this pioneering monograph channels discussions on race and education to create an essential practical resource for enacting real change on an everyday student level.
Keywords: Educational evaluation -- Great Britain.; Discrimination in higher education -- Great Britain.; Racism in higher education -- Great Britain.; Education -- Evaluation & Assessment.; Education: examinations and assessment.; elektronické knihy; electronic books